REVISING THE UNITARY VS. FEDERAL CLASSIFICATION (Journal of International Studies, 2022)
Over the last four decades, the distinction between unitary and federation systems has become increasingly blurred, as regionalization and decentralization have emerged as significant global trends. Regionalization and decentralization are responsible for redistribution of power across borders and for strengthening broader society's subnational capacity and function. Both have indirectly facilitated the expansion of "federalization processes" within unitary states. As a result, distinguishing between unitary and federated territorial management and power-sharing arrangements is difficult. This "intermediate system" was an apparently novel form of territorial division of power that was never classified as an incomplete federation or an evolutionary type of unitary system. This indicates that the unitary vs. federation dichotomy is becoming incongruous and that the existing classification is no longer relevant. As a result, this article revises the unitary-federal classification based on developments in n=70 selected countries from 1970 to 2018, as measured by the Regional Authority Index, an annual data series. To classify countries into clusters, the data index was analyzed using hybrid clustering analysis with k-means clustering as the primary analysis. Initially, inferential analysis performed suggested the establishment of four clusters (k=4). However, the clustering together of unitary and federated countries resulted in re-clustering, leading to the formation of five new clusters.